Science Batik Ciwaringin: The Implementation of Ethno-STEM PjBL Model in learning Biotechnology at PGSD Students. Issue 1 (March 2021) - Tresnawati, N; Saleh, I; Sudarmin,; Wardani, S
Abstract: Indonesian batik has been awarded by UNESCO as one of the world's non-object cultural heritages. And this is a challenge for young generation on how to preserve this culture. The purpose of this research is to implement Biotechnology learning through the Ethno-STEM PJBL model for PGSD students and produce sains batik, so it can triggger the young generation to preserve it. This learning model is a project based learning in analyzing several natural materials as natural dyes for batik, dye-making techniques that are integrated into the concept of biotechnology, and producing a product designed by the students. This research method is R&D research. It has 3 steps: (1) Define; (2) Design Development; and (3) Disseminate. The instruments used in this research are product validation sheets, assessment rubric products on the designs, colors, and symbolic value. Data were analyzed descriptive qualitative and descriptive statistics. The finding of the research showed that the products of sains batik validatated, one of which is "piperidine seribu daun" has a a secondary metabolite content of the mango combined with the design of thousand of leaves, the special Ciwaringin batik. It has a meaning of togetherness to preserve the environment for manga as local plant of Cirebon. The conclusion from this research is that students not only learn the concept of biotechnology but also they can develop Ciwaringin batik. The implication of this research is that it can stimulate the young generation to take a part in preserving and developing the Indonesian batik industry.